Changes in blood flow, portal pressure and shunting during the development of cirrhosis in response to beta-blockade. Issue 6 (June 1987) - McLaren, M; Braye, S; Fleming, J; Karran, S; Taylor, I
Abstract : An experimental model of cirrhosis was developed in the rat to assess the effect of disease and pharmacological manipulation on blood flow, shunting and portal pressure. With progression in the severity of histological cirrhosis there was a steady fall in effective liver blood flow as measured with radioisotope labelled colloid. This corresponded to a rise in portal pressure and shunting with a close correlation between the two (r = 0.7, p less than 0.01). In control animals and when portal hypertension was caused by extrahepatic obstruction, beta-blockade with propranolol, but not selective beta 2 blockade, significantly decreased liver blood flow. With cirrhosis there was a variable response to propranolol depending on the histological severity of disease, the height of portal pressure and degree of shunting. There is a possibility therefore that a potential may exist for lowering portal pressure by manipulating intrahepatic shunting.